2020
DOI: 10.3389/fnmol.2020.00090
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNA-146a Is a Wide-Reaching Neuroinflammatory Regulator and Potential Treatment Target in Neurological Diseases

Abstract: HIGHLIGHTS-Alterations in the microRNA-146a (miR-146a) level are common events in the pathogenesis of most neurological diseases.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
59
0
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 63 publications
(62 citation statements)
references
References 129 publications
(186 reference statements)
0
59
0
3
Order By: Relevance
“…Patterns of miRNA expression are complex -for example natural miRNA abundance has been shown to fluctuate during neural development and differentiation of the human brain and in the aging CNS (Giorgi Silveira et al, 2020;Ma et al, 2020;Wu and Kuo, 2020). Emerging data continue to support the concept that the analysis and characterization of specific miRNAs may be especially useful in the prodromal and pre-clinical phases of AD in which a very subtle pro-inflammatory neuropathology develops and molecular changes begin to accumulate even in the absence of the full-blown clinical symptoms as shown by the moderate and more advanced phases of AD (Hill and Lukiw, 2016;Bahlakeh et al, 2020;Fan et al, 2020;Ma et al, 2020;Wu and Kuo, 2020).…”
Section: Microrna (Mirna) Signaling In Admentioning
confidence: 99%
See 3 more Smart Citations
“…Patterns of miRNA expression are complex -for example natural miRNA abundance has been shown to fluctuate during neural development and differentiation of the human brain and in the aging CNS (Giorgi Silveira et al, 2020;Ma et al, 2020;Wu and Kuo, 2020). Emerging data continue to support the concept that the analysis and characterization of specific miRNAs may be especially useful in the prodromal and pre-clinical phases of AD in which a very subtle pro-inflammatory neuropathology develops and molecular changes begin to accumulate even in the absence of the full-blown clinical symptoms as shown by the moderate and more advanced phases of AD (Hill and Lukiw, 2016;Bahlakeh et al, 2020;Fan et al, 2020;Ma et al, 2020;Wu and Kuo, 2020).…”
Section: Microrna (Mirna) Signaling In Admentioning
confidence: 99%
“…These findings support the strengthening contention: (i) that brain-enriched miRNAs operate as fundamental components of an epigenetically controlled post-transcriptional signaling network in the mammalian CNS Kleaveland et al, 2018;Jaber et al, 2019;Eisen et al, 2020); and (ii) that miRNAs have an established capability to act independently, coordinately and/or cooperatively to create a highly sophisticated and interactive regulatory miRNA-mRNA network for families of brain genes that regulate many essential brain functions that are specifically altered in AD brain (Jaber et al, 2017;Kleaveland et al, 2018;Eisen et al, 2020;Lukiw, 2020a,b). Importantly, information-carrying ribonucleic acids such as highly soluble and mobile, single-stranded non-coding RNAs (sncRNAs) including microRNAs (miRNAs) can affect the operation of a large number of highly interactive pathogenic signaling pathways in the CNS, and represent strategic candidates for promoting AD onset, and for modulating or maintaining AD propagation and disease spread (Alexandrov et al, 2012;Chandrasekaran and Bonchev, 2016;Clement et al, 2016;Kleaveland et al, 2018;Lemcke and David, 2018;Hill, 2019;Jaber et al, 2019;Konovalova et al, 2019;Condrat et al, 2020;Fan et al, 2020;Kou et al, 2020).…”
Section: Traditional Pathophysiological Biomarkers For Ad Are Non-spementioning
confidence: 99%
See 2 more Smart Citations
“…These extruded vesicles were subsequently observed to be taken up by normal host brain microvascular endothelial cells, thereby inducing carcinogenic type phenotypic change in these brain cells, stimulating tumor invasion, proliferation and cancer spread mediated by endothelial cells of the neurovasculature (Hunter et al, 2008 [ 36 ]; Skog et al, 2008 [ 25 ]). Very recently, evidence has been provided showing that EXs and EMVs derived from miRNA-containing natural killer (NK) cells contribute to immunological surveillance and their provision of specific miRNAs may be the first-line of defense in the regulation of tumor cell growth, cytotoxicity and metastasis diffusion in the CNS (Briand et al, 2020 [ 8 ]; Federici et al, 2020 [ 62 ]). As discussed more fully below, it has recently been shown that brain EXs and EMVs released from diseased astrocytes and “activated microglia” carry specific miRNA-enriched cargoes, enriched in miRNA-34a and miRNA-125b for example, that contribute to neuropathological spreading and the exacerbation of neuropathological processes in AD, ALS, Parkinson’s disease (PD), Huntington’s disease (HD), stroke and other neuro-inflammatory degenerative conditions.…”
Section: Selective Micrornas In Exs and Emvsmentioning
confidence: 99%